Language Comprehension Developmental Milestones in Typically Developing Children Assessed by the New Language Phenotype Assessment (LPA) - Andrey Vyshedskiy; Ariella Pevzner; Brigid Mack; Eva Shrayer; Miranda Zea; Sasha Bunner; Nichole Wong; Elena Baskina; Amira Sheikh; Alessandro Tagliavia; Andriane Schmiedel Fucks; Andressa Schmiedel Sanches Santos; et al. (Children, 2025)
Background/Objectives: Three distinct language comprehension phenotypes have previously been identified in individuals with language deficits: (1) individuals with the Command Phenotype are limited to understanding simple commands; (2) individuals with the Modifier Phenotype demonstrate additional comprehension of combinations of nouns and adjectives; and (3) individuals with the Syntactic Phenotype possess full syntactic comprehension. We hypothesized that typically developing children progress through these same three language comprehension phenotypes and aimed to determine the typical age at which each phenotype emerges. Methods: To assess comprehension in young children, we developed the 15-item Language Phenotype Assessment (LPA). This tool uses toy-animal manipulatives to avoid reliance on picture interpretation and employs brief instructions to reduce auditory memory load. LPA items incorporate elements such as colors, sizes, numbers, spatial prepositions, and other syntactic components, posing novel combinations of words that children had not previously encountered. The LPA was administered to 116 typically-developing children aged 1.5–7 years, recruited by approaching parents in local parks and inviting them to participate. Results: Findings revealed a developmental trajectory consistent with the three previously described phenotypes: 50% of children attained the Command Phenotype by 1.6 years of age, the Modifier Phenotype by 3.0 years of age, and the Syntactic Phenotype by 3.7 years of age. All children acquired the Command Phenotype by 3, the Modifier Phenotype by 4, and the Syntactic Phenotype by 5 years of age. Conclusions: The LPA is an effective tool for assessing comprehension in children aged 1.5–5 years. It allows for the early identification of comprehension difficulties, supporting the timely initiation of appropriate language interventions.